Nine new Zingiber species (Zingiberaceae) from Vietnam - Leong-Skornickova, Jana; Nguyễn, Quốc Bình; Trần, Hữu Đăng; Šída, Otakar; Rybková, Romana; Trương, Bá Vương (Phytotaxa, 2015)
Nine new Zingiber species from Vietnam are reported here. Of these, Z. lecongkietii belongs to the sect. Cryptanthium, five species, Z. atroporphyreus, Z. cardiocheilum, Z. castaneum, Z. mellis and Z. plicatum, are terminally flowering species belonging to the sect. Dymczewiczia, and three species, Z. discolor, Z. microcheilum and Z. yersinii, belong to sect. Zingiber. Detailed descriptions, colour plates and preliminary IUCN assessments are given for all species. As the five terminally flowering novelties more than double the previously known number of species in the Z. sect. Dymczewiczia in Vietnam, a key to this section is provided.